Podocarpo, uma planta de interesse ornamental: propagação assexuada - Menegusso, Fernanda Jaqueline (2018)
The objective of this study was to evaluate the potential of rooting of podocarpos cuttings in function of the number of leaves, concentrations of IBA and other phytorregulators, different application methods and cutting season. Two experiments were carried out under weaning conditions, in a factorial scheme containing 3 replicates of 15 cuttings, the first with 4 concentrations of IBA (0, 500, 1000 and 1500 mg L-1), 3 numbers of leaves at the cuttings (4, 6, 8) and 2 seasons (winter and summer). These were removed in August/2016 and January/2017, prepared with 10 cm in length and immersed in solutions for 10 s. In the second experiment three types of phytoregulators (IBA, NAA and IAA) and 2 application forms were tested (slow and quick immersion). Cuttings were prepared in the same manner as in the first experiment, maintaining 4 leaves. The bases of the cuttings were immersed for 10 s and 24 h in the solutions, then taken to root in sand bed. After 100 days of experimentation, it was concluded that podocarp cuttings collected in the summer had a higher percentage of rooting, 4 leaves and IBA concentration should be maintained between 750 and 800 mg L-1. The best form of application of phytoregulator is by rapid immersion.